Impact of Procedure Volume on the Outcomes of Surgical Aortic Valve Replacement - Oettinger, Vera; Kaier, Klaus; von zur Mühlen, Constantin; Zehender, Manfred; Bode, Christoph; Beyersdorf, Friedhelm; Stachon, Peter; Bothe, Wolfgang (The Thoracic and Cardiovascular Surgeon, 2022)
Background Literature demonstrated that procedure volumes affect outcomes of patients undergoing transcatheter aortic valve implantation. We evaluated the outcomes of surgical aortic valve replacement.Methods All isolated surgical aortic valve replacement procedures in Germany in 2017 were identified. Hospitals were divided into five groups from ≤25 (very low volume) until >100 (very high volume) annual procedures.Results In 2017, 5,533 patients underwent isolated surgical aortic valve replacement. All groups were of comparable risk (logistic EuroSCORE, 5.12–4.80%) and age (66.6–68.1 years). In-hospital mortality and complication rates were lowest in the very high-volume group. Multivariable logistic regression analyses showed no significant volume–outcome relationship for in-hospital mortality, stroke, postoperative delirium, and mechanical ventilation > 48 hours. Regarding acute kidney injury, patients in the very high-volume group were at lower risk than those in the very low volume group (odds ratio [OR] = 0.53, p = 0.04). Risk factors for in-hospital mortality were previous cardiac surgery (OR = 5.75, p < 0.001), high-grade renal disease (glomerular filtration rate < 15 mL/min, OR = 5.61, p = 0.002), surgery in emergency cases (OR = 2.71, p = 0.002), and higher grade heart failure (NYHA [New York Heart Association] III/IV; OR = 1.80, p = 0.02). Risk factors for all four complication rates were atrial fibrillation and diabetes mellitus.Conclusion Patients treated in very low volume centers (≤25 operations/year) had a similar risk regarding in-hospital mortality and most complications compared with very high-volume centers (>100 operations/year). Only in the case of acute kidney injury, very high-volume centers showed better outcomes than very low volume centers. Therefore, surgical aortic valve replacement can be performed safely independent of case volume.
Keywords: surgical aortic valve replacement; volume–outcome relationship; caseload; in-hospital mortality; complications; transcatheter aortic valve implantation